Phương pháp phân rã giải qui hoạch lõm - Tam, Bui The; Tuc, Tran (Journal of Computer Science and Cybernetics, 2018)
In this paper a decomposition method is presented for solving a class of concave minimization problems with special structure. In each of these problems, the  total number of variables may be fairly large, but only relatively few variables are actually responsible for the nonlinearity of the objective function.